Rozkład naprężeń cieplnych w belce z płaską szczeliną - NARAIN, Prem (Engineering Transactions, 1966)
Distribution of thermal stresses in a beam with a plane crack The stress distribution in the vicinity of a Griffith type of crack situated in a rectangular beam of isotropic homogeneous elastic material occupying the region –δ ≤ x ≤ δ, –π ≤ y ≤ π –∞ ≤ z ≤ ∞ has been discussed, when the beam is subject to an internal pressure in the crack and a thermal field, under the usual assumptions of infinitesimal theory of elasticity appropriate to the plane strain. Use is made of the technique developed by Srivastav [1] for solving dual series relations.